Relationship between the design height of the shelves in industrial warehouses and their heat release rate. Issue 3 (2015) - Fera, M.; Fruggiero, F.; Lambiase, A.; Macchiaroli, R.; Miranda, S.
Abstract: In the last decades, fire safety engineering (FSE) has been extensively used to improve the design of many industrial systems. In this study, the FSE approach is applied to determine the optimal vertical distance between pallets allocated in a warehouse containing plastic materials in order to control and reduce typical fire parameter such as the heat release rate (HRR). Moreover, the study reported in this paper is used to confirm that the design rules indicated by current EN norms for automated fire extinguishing systems are well effective to limit the fire risk and ensure proper safety conditions.